If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(4b + 3) + (9b + -1) = 0 Reorder the terms: -2(3 + 4b) + (9b + -1) = 0 (3 * -2 + 4b * -2) + (9b + -1) = 0 (-6 + -8b) + (9b + -1) = 0 Reorder the terms: -6 + -8b + (-1 + 9b) = 0 Remove parenthesis around (-1 + 9b) -6 + -8b + -1 + 9b = 0 Reorder the terms: -6 + -1 + -8b + 9b = 0 Combine like terms: -6 + -1 = -7 -7 + -8b + 9b = 0 Combine like terms: -8b + 9b = 1b -7 + 1b = 0 Solving -7 + 1b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 1b = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 1b = 0 + 7 1b = 0 + 7 Combine like terms: 0 + 7 = 7 1b = 7 Divide each side by '1'. b = 7 Simplifying b = 7
| 5a-5-15=3a+6+4 | | 42+1x+x^2=0 | | 40+28t+4t^2=0 | | -8=-2x-6x | | 2-1.5x=11 | | 2p-4p=-8 | | 4x+4y=5v | | 12y+14y= | | n^2-40=-3n | | n^2-40= | | 35x-5= | | y=sin(st) | | 8x-6x-4x= | | 6(m-2)-2(m+1)=0 | | 3+49x=28x+27 | | 1.5(a-1)-15=3(a+2)+4 | | (x^2-4)(2x+1)(1-x)=0 | | B-2(1+3b)=4b-29 | | 4cos(x)= | | (5b-7)-2(2b+4)=-4 | | (3u+8)5= | | -2(x+5)=-2(x-2)+5 | | lnx=-4.3 | | 5(x-1)-15=3(x+2)+4 | | 2y^2+3y-3=0 | | 7(5+4)= | | 1.5q=-4.8 | | m-3k=pfork | | g-7=22 | | 4(x+3)+6=4x+9 | | 2x+z=6 | | -x+y=zforx |